Hubungan Pola Makan, Status Gizi, dan Tingkat Stres dengan Hipertensi di Wilayah Kerja Puskesmas Pantai Hambawang - Yuliatil Lail; Sigit Yudistira (Jurnal Kesehatan Indonesia, 2021)
A person had hypertension if the systolic blood pressure is 140 mmHg and diastolic blood pressure is 90 mmHg. Hypertension is strongly influenced by factors such as age, gender, dietary patterns, nutritional status, and stress levels. This study aimed to analyze the relation of dietary patterns, nutritional status, and stress levels to hypertension in the working area of ​​Hambawang Beach Public Health Center. This study used an observational method with a cross-sectional design. The statistical analysis used was the Spearman's rank test. The results of this study indicated that the stress level was associated with the incidence of hypertension (p=0.044). Factors that had no association with the incidence of hypertension were fat consumption (p=0.881), sodium consumption (p=0.816), potassium consumption (p=0.986) and nutritional status (p=0.171). Respondents were expected to have a healthy lifestyle such as frequent exercise and good rest habits, limiting the consumption of fat, sodium and balanced with potassium consumption, mental relaxation to foster positive emotions and maintain nutritional status.